A map of the United States and Canada, New-Scotland, New-Brunswick and New-Foundland = Carte des Etats-Unis avec le Canada, la Nouvelle Ecosse, le Nouveau Brunswick & Terre-Neuve / dressée par Lapie. - Lapie, M. (Pierre), 1779-1850 (1806)
Covers eastern portion of North America from Newfoundland to the northern part of South America.; Relief shown by hachures.; In lower margin: Déposée à la Bibliothèque Impériale le 5 Septembre 1806.; Title in French and English; place names in French.; Title from cartouche in upper right corner.; "Ecrit par J.J. Pachoux."; Prime meridian: Paris.; Colored to show colonial possessions. Color 1:6,000,000